Dairy fortification as a good option for dietary nutrition status improvement of 676 preschool children in China: A simulation study based on a cross-sectional diet survey (2018–2019) - Ding, Ye; Han, Fei; Xie, Zhencheng; Li, Genyuan; Zhuang, Yiding; Yin, Jia; Fu, Mingxian; You, Jialu; Wang, Zhixu (Frontiers in Nutrition, 2022)
Chinese children are deficient in several essential nutrients due to poor dietary choices. Dairy products are a source of many under-consumed nutrients, but preschool children in China consume dairy products significantly less than the recommended level. From the cross-sectional dietary intake survey of infants and young children aged 0-6 years in China (2018–1019), preschool children (age: 3–6 years) (n=676) were selected. The four-day dietary data (including 2 working days and 2 weekends) collected through an online diary with reference to the food atlas were used for analysis and simulation. In scenario 1, individual intake of liquid milk equivalents was substituted at a corresponding volume by soymilk, cow’s milk, or formulated milk powder for preschool children (FMP-PSC). In scenario 2, the amount of cow’s milk or FMP-PSC increased to ensure each child’s dairy intake reached the recommended amount (350 g/day). In both scenarios, the simulated nutrient intakes and nutritional inadequacy or surplus were compared to the survey’s actual baseline data. The results suggested that replacing dairy foods with FMP-PSC at matching volume is better than replacing them with soymilk or cow’s milk to increase the intake of DHA, calcium, iron, zinc, iodine, vitamin A, vitamin B1, vitamin B3, vitamin B12, vitamin C and vitamin D. Moreover, our results suggested that adding FMP-PSC to bring each child’s dairy intake to the recommended amount can bring the intakes of dietary fiber, DHA, calcium, iron, zinc, iodine, vitamin A, vitamin B1, vitamin B3, vitamin B9, vitamin B12, vitamin C and vitamin D more in line with the recommendations when compared with cow’s milk. Therefore, accurate nutrition information should be provided to the parents of preschool children so as to guide their scientific consumption of dairy products and the usage and addition of fortified dairy products can be encouraged as needed.